2011
DOI: 10.1002/hep.24576
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Hedgehog pathway is associated with cellular permissiveness for hepatitis C virus replication

Abstract: Studies of the Hepatitis C virus (HCV) life-cycle rely heavily upon Huh7.5 cells, but the reasons why these cells are exceptionally permissive for HCV replication are not clear. Based on recent clinical observations, we hypothesized that the Hedgehog (Hh) pathway, which has not been previously associated with HCV replication, may be involved in the Huh7.5 phenotype of increased permissiveness. We tested this hypothesis by comparing levels of a variety of Hh related cellular markers in Huh7.5 cells with the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
(48 reference statements)
0
42
0
Order By: Relevance
“…We had previously reported that permissiveness of HCV replication was associated with increased Hedgehog (Hh) activity (15), and that inhibition of Hh signaling led to a reduction in cell-associated HCV RNA levels. Consistently, we find that basal expression of OPN, a Hh-regulated target gene and a proximal effector of the Hh pathway (8), is 30-fold higher in Huh7.5 than Huh7 cells (Fig 1B–C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We had previously reported that permissiveness of HCV replication was associated with increased Hedgehog (Hh) activity (15), and that inhibition of Hh signaling led to a reduction in cell-associated HCV RNA levels. Consistently, we find that basal expression of OPN, a Hh-regulated target gene and a proximal effector of the Hh pathway (8), is 30-fold higher in Huh7.5 than Huh7 cells (Fig 1B–C).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with SAG (associated with increased HCV RNA (15)) led to a 2-fold increase in OPN mRNA, while inhibiting the Hh pathway (associated with reduced HCV RNA) repressed OPN mRNA to basal (control) levels. The aggregate data supports our hypothesis that OPN supports HCV replication in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…41 GDC-0449 has anti-hepatitis C virus (HCV) activity in a dose-dependent manner in human HCC cell line Huh 7.5. 42 Vismodegib reduced TNFrelated apoptosis-inducing ligand-mediated liver injury in mouse model. 43 Furthermore, GDC-0449 alters the homeostasis of intracellular Ca 21 , inhibits cell growth, and reduces side population in lung cancer.…”
Section: Gdc-0449 Is a Potent Smo Inhibitor And The Blockade Ofmentioning
confidence: 99%